2021
DOI: 10.1016/j.heliyon.2021.e07642
|View full text |Cite
|
Sign up to set email alerts
|

Class and landscape level habitat fragmentation analysis in the Bale mountains national park, southeastern Ethiopia

Abstract: BackgroundThe changes of landscape structure and function due to human interference is hastening worldwide, and it is compulsory to preserve biological resources in a protected system. This study aims to measure the landscape ecological structure and the extent of habitat fragmentation in the Bale mountains national park. The land use/land cover change was determined by interpreting the 1985, 1995, 2005 and 2017 Landsat images with ArcGIS 10.3, and the selected landscape structural metrics was analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…(2018) also supported that shrub land was the dominant land cover from 1985 to 2015 in Hugumburda National forest priority areas that declined. Farmland expansion at the expense of woodland decline was also stated in Bale Mountain National Park ( Muhammed and Elias, 2021 ; Solomon et al., 2014 ). Shrub land, grass (grazing land), settlement, cultivation, and bare land increased as the cost of forestland declined ( Asmame and Abegaz, 2017 ).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…(2018) also supported that shrub land was the dominant land cover from 1985 to 2015 in Hugumburda National forest priority areas that declined. Farmland expansion at the expense of woodland decline was also stated in Bale Mountain National Park ( Muhammed and Elias, 2021 ; Solomon et al., 2014 ). Shrub land, grass (grazing land), settlement, cultivation, and bare land increased as the cost of forestland declined ( Asmame and Abegaz, 2017 ).…”
Section: Resultsmentioning
confidence: 89%
“…A study in PAs of Mexico also indicated a reduction in temperate and tropical vegetation cover threatened to the whole biodiversity of the site ( Sancheza Reyes et al., 2017 ). A recent study in Bale Mountain National Park revealed that the decreasing trends of grassland and forestland while increasing farmland LULC led to increased habitat fragmentation and reduced the size and loss of available core area for the existing core-dependent endemic wildlife species ( Muhammed and Elias, 2021 ). Furthermore, the expansion of agriculture threatens elephant habitats and increases competition for resources between humans and elephants ( Sintayehu and Kassaw, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…It might be attributed to the combined effects of anthropogenic and edaphic differences, as the representative plots were composed of three land-use types (Forest, Agroforestry, and cultivated land) and the concomitant occurrence of species adapted to these different environmental conditions. The difference in terrain, soils, water, and microclimatic conditions cause differences in species adaptability [ 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of its huge potential and ecological importance, habitat degradation takes place at an alarming rate in different agro-climatic zones and poses a severe threat to the ecosystem [ 13 ]. The BMNP's landscape structure is gradually fragmenting, and human activities such as settlement expansion and subsistence agriculture have an impact on plant diversity and composition [ 14 ]. Many of the studies in the BMNP focuses on the extent of land use/land cover change and its effect on plant diversity and structure.…”
Section: Introductionmentioning
confidence: 99%